Research on weak greedy routing over graph embedding for wireless sensor networks - LI Zhi-gang1; CHEN Wei-wei1; XIAO Nong2; XIA Ge-ming2 (Tongxin xuebao)
The greedy routing in sensor networks can be classified into two categories,strong greedy routing and weak greedy routing.The weak greedy routing protocol needs geographic location and strong greedy routing needs greedy em-bedding network.In order to solve these problems and minimize operation complexity and energy overhead,a light-weight tree-based network embedding graph（TNEG） was proposed and over the TNEG,a local monotone function was designed and two routing rules were proposed,then two weak greedy routing protocols,TGR and biTGR were de-signed.The simulation shows two protocols achieve good performance on path stretch factor and load balance factor.